CeO2-loaded NiCo-LDH nano-catalyst and preparation method thereof

By introducing CeO2 into NiCo-LDH, the CeO2-supported NiCo-LDH nanocatalyst is formed, which solves the problems of complex preparation process and insufficient material performance in the prior art, and achieves efficient OER catalytic performance and the possibility of large-scale production.

CN119287431APending Publication Date: 2025-01-10SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411416902.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing NiCo-LDH electrocatalyst is complex and costly, resulting in large particle size, small specific surface area, and uneven morphology, which limits its application in OER.

Method used

CeO2 is used as doping source, and CeO2 is introduced into NiCo-LDH by co-precipitation method. Urea is used as a precipitant and reflux reaction is carried out under stirring conditions to form a CeO2-supported NiCo-LDH nanocatalyst, which improves its conductive properties and active positions. point.

Benefits of technology

The preparation of high crystallization and high purity CeO2-supported NiCo-LDH nanocatalyst has been achieved, with ultra-thin 2D nanosheet structure and excellent electrocatalytic properties. It is suitable for large-scale production and improves the charge transfer efficiency of OER.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287431A_ABST
    Figure CN119287431A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano materials, and discloses a CeO2 loaded NiCo-LDH nano catalyst and a preparation method thereof. The preparation method comprises the following steps: dispersing a doping source cerium salt, a nickel salt and a cobalt salt in a reaction solvent to obtain a metal salt solution; uniformly dispersing a precipitant urea in the metal salt solution to obtain a mixed solution; the mixed solution is subjected to a reflux reaction at 85-95 DEG C, so that nickel ions and cobalt ions provided by the nickel salt and the cobalt salt are subjected to a precipitation reaction with urea to form NiCo-LDH, cerium salt is converted into CeO2 on the surface of NiCo-LDH in a nano-particle form, and the CeO2-loaded NiCo-LDH nano-catalyst is obtained. The preparation method disclosed by the invention is low in reaction temperature, short in reaction time and simple and can be used for large-scale production; the prepared catalyst has excellent electronic conductivity and excellent electro-catalytic performance, and is beneficial to popularization and large-scale production and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a CeO2-loaded NiCo-LDH nanocatalyst and a preparation method thereof. Background Art

[0002] Water electrolysis is a process that converts electrical energy into chemical energy, including two half reactions: the hydrogen evolution reaction at the cathode and the oxygen evolution reaction at the anode. Among them, the oxygen evolution reaction at the anode is Oxygen Evolution Reaction, referred to as OER. OER is the key limiting factor in the efficiency of water electrolysis because it is a four-electron transfer process with slow reaction kinetics and requires a very high overvoltage to drive the reaction. Therefore, an electrocatalyst needs to be provided to promote the occurrence of OER.

[0003] However, the electrocatalysts currently used are mainly iridium-based and ruthenium-based electrocatalysts. Although iridium-based and ruthenium-based electrocatalysts have good catalytic activity, they are expensive and scarce, which restricts their large-scale application. Therefore, it is urgent to develop low-cost, high-catalytic activity, stable and environmentally friendly electrocatalysts for OER. Layered double hydroxides, also known as LDHs, have been widely studied as electrocatalysts for water splitting due to their large interlayer space and significant redox properties. The two-dimensional structure of LDHs is conducive to charge transfer in electrochemical processes. Due to their unique structure and properties, LDHs such as NiCo-LDH, MnCo-LDH, CoAl-LDH, NiMn-LDH, NiNi-alloy and NiNi-LDH have been proven to be very effective for OER applications.

[0004] NiCo-LDH is currently the main electrocatalyst used in OER due to its advantage of high electrocatalytic intrinsic activity. The main preparation methods used in the prior art for preparing NiCo-LDH include hydrothermal method, template method, in-situ growth method on conductive substrate, electrochemical deposition, etc. However, these methods have complicated preparation processes and high costs, and are not suitable for large-scale production; moreover, the NiCo-LDH obtained by the above methods is prone to agglomeration during the preparation process, resulting in a larger particle size, a smaller specific surface area, and an uneven morphology of the obtained material, which leads to defects such as untimely charge transfer in the reaction process in the prepared NiCo-LDH in practical applications, thereby limiting the further application of NiCo-LDH as a catalyst. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a CeO2-loaded NiCo-LDH nanocatalyst and a preparation method thereof. The present invention uses nickel salt and cobalt salt as the basis for constructing NiCo-LDH, uses cerium salt as a doping source, and uses urea as a precipitant. The cerium salt, nickel salt and cobalt salt are mixed in a reaction solvent and then urea is added, and then a reflux reaction is performed under stirring conditions, so that the nickel ions and cobalt ions provided by the nickel salt and cobalt salt react with urea to form NiCo-LDH by precipitation reaction, and at the same time, the cerium salt is converted into CeO2 in the form of nanoparticles on the surface of NiCo-LDH, thereby obtaining the CeO2-loaded NiCo-LDH nanocatalyst.

[0006] The CeO2-loaded NiCo-LDH nanocatalyst and the preparation method thereof of the present invention are achieved by the following technical scheme:

[0007] The first object of the present invention is to provide a method for preparing a CeO2-loaded NiCo-LDH nanocatalyst.

[0008] It should be noted that in order to ensure the catalytic activity of the catalyst itself, the present invention preferably uses NiCo-LDH as the matrix material for preparing the catalyst, so as to modify and dope the NiCo-LDH material by introducing metal cations into the NiCo-LDH material, thereby adjusting the crystallinity and size of the NiCo-LDH layer.

[0009] In the process of screening metal cation oxides, the present invention takes into account that Ce oxide CeO2 can undergo reversible redox reactions under mild conditions and has excellent storage and oxygen release properties. Therefore, the present invention prefers CeO2 as the doped metal cation oxide, so as to improve the conductivity and active sites of the NiCo-LDH material by doping CeO2 in the NiCo-LDH material.

[0010] In order to ensure that CeO2 can be successfully doped into NiCo-LDH materials, the present invention improves the conductivity and active sites of NiCo-LDH materials through CeO2, thereby enabling NiCo-LDH materials to be applied in the field of electrocatalysis. The present invention is specifically implemented by the following steps:

[0011] Step 1, preparation of metal salt solution:

[0012] The cerium salt is used as a doping source, and the cerium salt, nickel salt and cobalt salt are uniformly dispersed in a reaction solvent to obtain a metal salt solution.

[0013] It should be noted that in order to simplify the preparation process, the present invention preferably adopts a co-precipitation method, by uniformly dispersing the cerium salt, nickel salt and cobalt salt in the reaction solvent so that the cerium salt, nickel salt and cobalt salt are fully in contact, which is beneficial to the subsequent formation of NiCo-LDH. The Ce ions provided by the cerium salt can undergo a precipitation reaction under the action of the precipitant, and then be converted into CeO2 and uniformly doped in NiCo-LDH, thereby obtaining a NiCo-LDH nanocatalyst loaded with CeO2 with uniform component distribution. The preparation method of the present invention can effectively improve the yield of the NiCo-LDH nanocatalyst loaded with CeO2, and can be used for large-scale production.

[0014] The present invention does not limit the specific type of the cerium salt used, as long as it can provide cerium ions. In some feasible embodiments of the present invention, the cerium salt used can be selected from one or more of cerium chloride, cerium nitrate and cerium sulfate.

[0015] The present invention does not limit the specific type of nickel salt used, as long as it can provide nickel ions. In some feasible embodiments of the present invention, the nickel salt used can be selected from one or more of nickel nitrate, nickel sulfate and nickel chloride.

[0016] The present invention does not limit the specific type of the cobalt salt used, as long as it can provide cobalt ions. In some feasible embodiments of the present invention, the cobalt salt used can be selected from one or more of cobalt nitrate, cobalt sulfate and cobalt chloride.

[0017] In order to ensure that the doped cerium salt can be doped into NiCo-LDH and obtain a CeO2-loaded NiCo-LDH nanocatalyst with uniform component distribution, in some preferred embodiments of the present invention, the molar ratio of the nickel salt, the cobalt salt and the cerium salt is 1:1:0.1-0.5.

[0018] In order to ensure that the cerium salt is in full contact with the nickel salt and the cobalt salt, the cerium salt, the nickel salt and the cobalt salt need to be fully dissolved in the solvent, so the solvent used needs to have good solubility for the cerium salt, the nickel salt and the cobalt salt. Therefore, the present invention preferably uses a mixed solvent obtained by mixing ethylene glycol and water in a volume ratio of 2 to 3:1 as the reaction solvent. And in order to further ensure that the mixed solution of ethylene glycol and water can fully dissolve the cerium salt, the nickel salt and the cobalt salt, in some preferred embodiments of the present invention, the ratio of the mixed solution of ethylene glycol and water to the cerium salt is 50mL to 55mL: 0.375mmol to 1.875mmol.

[0019] Step 2, preparation of mixed solution:

[0020] Urea is used as a precipitant and is uniformly dispersed in the metal salt solution to obtain a mixed solution.

[0021] It should be noted that the present invention uses urea as a precipitant to make it fully contact with various metal ions to prepare for the subsequent formation of CeO2-loaded NiCo-LDH nanocatalysts. Moreover, urea is hydrolyzed after being dispersed in the metal salt solution, so that the pH value of the solution system tends to be uniform and gradually increases, thereby providing an alkaline environment for the solution system, which is conducive to accelerating the growth rate of LDHs crystals and obtaining highly crystalline and high-purity CeO2-loaded NiCo-LDH nanocatalysts; and the size of the obtained CeO2-loaded NiCo-LDH nanocatalyst is 10nm to 100nm.

[0022] In order to ensure that urea can undergo a precipitation reaction during the subsequent reflux reaction, in some feasible embodiments of the present invention, the molar ratio of urea to cobalt salt is 0.037-0.038:1.

[0023] In order to ensure that urea and various metal ions can be uniformly stirred, in some feasible embodiments of the present invention, ultrasonic coordinated stirring is used for dispersion, and the ultrasonic power is 600W to 800W, and the ultrasonic time is 10min to 30min.

[0024] Step 3, forming CeO2-supported NiCo-LDH nanocatalyst by reflux reaction:

[0025] Under stirring conditions, the mixed solution is subjected to a reflux reaction at 85° C. to 95° C. During the reflux reaction, as the temperature of the reaction system increases, nickel ions provided by the nickel salt and cobalt ions provided by the cobalt salt react with urea to form NiCo-LDH under the alkaline environment provided by urea. At the same time, the cerium salt is uniformly attached to the surface of NiCo-LDH and converted into CeO2 in the form of particle precipitation, thereby obtaining the CeO2-loaded NiCo-LDH nanocatalyst.

[0026] It should be noted that, in order to ensure that the CeO2-loaded NiCo-LDH nanocatalyst can be obtained through the reflux reaction, in some preferred embodiments of the present invention, the reflux reaction time is 4h to 8h.

[0027] It can be understood that since the reflux reaction is carried out in a solvent environment, the target product obtained, namely the CeO2-loaded NiCo-LDH nanocatalyst, also exists in the solvent environment. In order to facilitate the utilization of the target product, the reaction liquid obtained by the reflux reaction needs to be post-treated, that is, the reaction liquid needs to be firstly subjected to solid-liquid separation to obtain a solid component, and then the solvent and other impurities remaining on the surface of the solid component are removed by washing, and then dried to remove the detergent used for washing, so as to obtain a pure CeO2-loaded NiCo-LDH nanocatalyst.

[0028] Among them, in some preferred embodiments of the present invention, for the convenience of operation, centrifugation is used for solid-liquid separation. After removing the supernatant, ethanol and deionized water are added to continue centrifugation, and the operation is repeated until the pH of the supernatant is 6.8-7.2.

[0029] In some preferred embodiments of the present invention, the drying temperature is 55° C. to 65° C., and the drying time is 8 h to 12 h.

[0030] The second object of the present invention is to provide a CeO2-loaded NiCo-LDH nanocatalyst prepared by the above preparation method.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention uses nickel salt and cobalt salt as the basis for constructing NiCo-LDH, and uses cerium salt as the doping source; by first dispersing cerium salt, nickel salt and cobalt salt in a reaction solvent, the dispersibility of cerium salt, nickel salt and cobalt salt is improved, thereby reducing the agglomeration phenomenon in the LDH preparation process. Urea is then used as a precipitant, added and mixed to obtain a mixed solution, so that urea is fully in contact with each metal ion, in preparation for the subsequent formation of CeO2-loaded NiCo-LDH nanocatalyst; moreover, urea is hydrolyzed after being dispersed in the metal salt solution, thereby making the pH value of the solution system tend to be uniform and gradually increase, thereby providing an alkaline environment for the solution system. The mixed solution is then subjected to a reflux reaction at 85°C to 95°C under stirring conditions, so that the nickel ions provided by the nickel salt and the cobalt ions provided by the cobalt salt react with urea to form NiCo-LDH under the alkaline environment provided by urea. At the same time, the Ce ions provided by the cerium salt are uniformly attached to the surface of the NiCo-LDH and converted into CeO2 in the form of particle precipitation. With the formation of CeO2, an electron transport channel from the CeO2 particles to the LDH is constructed, which is more conducive to the catalytic reaction, thereby obtaining a highly crystalline and high-purity CeO2-loaded NiCo-LDH nanocatalyst.

[0033] The present invention uses an ethylene glycol-water system as a reaction solvent, which can effectively improve the dispersibility of cerium salt, nickel salt and cobalt salt, thereby reducing or avoiding the agglomeration phenomenon in the LDH preparation process, thereby increasing the active surface area and utilization rate of the catalyst. In addition, the addition of ethylene glycol allows Ni and Co to ensure a better crystal form in an alkaline environment and generate large sheets of layered structure NiCo-LDH.

[0034] The CeO2-loaded NiCo-LDH nanocatalyst obtained by the present invention has an ultrathin 2D nanosheet structure, and some pore structures that are beneficial to electrolyte diffusion are also found on the ultrathin 2D nanosheet structure. These defect structures provide more active sites and adsorption centers for the catalyst, which not only helps to load Ce single atoms, but also accelerates the charge transfer during the water electrolysis reaction, so that the catalyst has higher electronic conductivity and excellent electrocatalytic performance.

[0035] The preparation method of the invention has low reaction temperature, short reaction time and simple method, which is conducive to promotion and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is Ce of Example 2 0.2 / NiCo-LDH, Ce of Example 4 0.4 / NiCo-LDH, Ce of Example 5 0.5 / NiCo-LDH and NiCo-LDH of Comparative Example 2.

[0037] Figure 2 TEM image of NiCo-LDH of Comparative Example 2.

[0038] Figure 3 is Ce of Example 4 0.4 TEM image of / NiCo-LDH.

[0039] Figure 4 is Ce of Example 5 0.5 TEM image of / NiCo-LDH.

[0040] Figure 5 is Ce of Example 2 0.2 / NiCo-LDH, Ce of Example 4 0.4 / NiCo-LDH, Ce of Example 5 0.5 / NiCo-LDH and OER performance test results of NiCo-LDH of comparative example 2. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0042] Example 1

[0043] This embodiment provides a CeO2-loaded NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0044] Step 1, preparation of metal salt solution:

[0045] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0046] 2) 3.75 mmol of Ni(NO3)2·6H2O, 3.75 mmol of Co(NO3)2·6H2O and 0.375 mmol of CeCl3·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0047] Step 2, preparation of mixed solution:

[0048] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred, and the mixed system was ultrasonicated at 700 W for 20 min to obtain a uniformly dispersed mixed solution.

[0049] Step 3, forming CeO2-supported NiCo-LDH nanocatalyst by reflux reaction:

[0050] The mixed solution was stirred and refluxed for 6 hours in an oil bath reaction condition at 90°C, and the solid component was obtained by centrifugation, and the solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining CeO2-supported NiCo-LDH nanocatalyst. The yield was 16.39%.

[0051] Since the amount of Ce salt used in this example is 0.1 of the amount of Ni salt used, that is, the doping amount relative to the Ni salt is 0.1, the CeO2-loaded NiCo-LDH nanocatalyst obtained in this example is marked as Ce 0.1 / NiCo-LDH.

[0052] Example 2

[0053] This embodiment provides a CeO2-loaded NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0054] Step 1, preparation of metal salt solution:

[0055] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0056] 2) 3.75 mmol of Ni(NO3)2·6H2O, 3.75 mmol of Co(NO3)2·6H2O and 0.75 mmol of CeCl3·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0057] Step 2, preparation of mixed solution:

[0058] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred, and the mixed system was ultrasonicated for 20 minutes to obtain a uniformly dispersed mixed solution.

[0059] Step 3, forming CeO2-supported NiCo-LDH nanocatalyst by reflux reaction:

[0060] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a CeO2-loaded NiCo-LDH nanocatalyst.

[0061] That is, the difference between this embodiment and embodiment 1 is only that:

[0062] In this example, the amount of Ce salt used is 0.2 relative to the doping amount of Ni salt, so the CeO2-loaded NiCo-LDH nanocatalyst obtained in this example is marked as Ce 0.2 / NiCo-LDH.

[0063] Example 3

[0064] This embodiment provides a CeO2-loaded NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0065] Step 1, preparation of metal salt solution:

[0066] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0067] 2) 3.75 mmol of Ni(NO3)2·6H2O, 3.75 mmol of Co(NO3)2·6H2O and 1.125 mmol of CeCl3·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0068] Step 2, preparation of mixed solution:

[0069] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred, and the mixed system was ultrasonicated for 20 minutes to obtain a uniformly dispersed mixed solution.

[0070] Step 3, forming CeO2-supported NiCo-LDH nanocatalyst by reflux reaction:

[0071] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a CeO2-loaded NiCo-LDH nanocatalyst.

[0072] That is, the difference between this embodiment and embodiment 1 is only that:

[0073] In this example, the amount of Ce salt used is 0.3 relative to the doping amount of Ni salt, so the CeO2-loaded NiCo-LDH nanocatalyst obtained in this example is marked as Ce 0.3 / NiCo-LDH.

[0074] Example 4

[0075] This embodiment provides a CeO2-loaded NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0076] Step 1, preparation of metal salt solution:

[0077] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0078] 2) 3.75 mmol of Ni(NO3)2·6H2O, 3.75 mmol of Co(NO3)2·6H2O and 1.5 mmol of CeCl3·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0079] Step 2, preparation of mixed solution:

[0080] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred. At the same time, the mixed system was ultrasonicated at an ultrasonic power of 700 W for 20 minutes to obtain a uniformly dispersed mixed solution.

[0081] Step 3, forming CeO2-supported NiCo-LDH nanocatalyst by reflux reaction:

[0082] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a CeO2-loaded NiCo-LDH nanocatalyst.

[0083] That is, the difference between this embodiment and embodiment 1 is only that:

[0084] In this example, the amount of Ce salt used is 0.4 relative to the doping amount of Ni salt, so the CeO2-loaded NiCo-LDH nanocatalyst obtained in this example is marked as Ce 0.4 / NiCo-LDH.

[0085] Example 5

[0086] This embodiment provides a CeO2-loaded NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0087] Step 1, preparation of metal salt solution:

[0088] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0089] 2) 3.75 mmol of Ni(NO3)2·6H2O, 3.75 mmol of Co(NO3)2·6H2O and 1.875 mmol of CeCl3·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0090] Step 2, preparation of mixed solution:

[0091] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred, and the mixed system was ultrasonicated at an ultrasonic power of 700 W for 20 min to obtain a uniformly dispersed mixed solution.

[0092] Step 3, forming CeO2-supported NiCo-LDH nanocatalyst by reflux reaction:

[0093] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a CeO2-loaded NiCo-LDH nanocatalyst.

[0094] That is, the difference between this embodiment and embodiment 1 is only that:

[0095] In this example, the amount of Ce salt used is 0.5 relative to the doping amount of Ni salt, so the CeO2-loaded NiCo-LDH nanocatalyst obtained in this example is marked as Ce 0.5 / NiCo-LDH.

[0096] Comparative Example 1

[0097] This comparative example provides a NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0098] Step 1, preparation of metal salt solution:

[0099] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0100] 2) 2.5 mmol of Ni(NO3)2·6H2O and 5 mmol of Co(NO3)2·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0101] Step 2, preparation of mixed solution:

[0102] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred. At the same time, the mixed system was ultrasonicated at an ultrasonic power of 700 W for 20 minutes to obtain a uniformly dispersed mixed solution.

[0103] Step 3, forming NiCo-LDH nanocatalyst by reflux reaction:

[0104] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a NiCo-LDH nanocatalyst.

[0105] That is, the difference between this comparative example and Example 1 is only that:

[0106] In this comparative example, no Ce salt is added, and the molar ratio of Ni salt to Co salt in this comparative example is 1:2, so the NiCo-LDH nanocatalyst obtained in the comparative example is marked as NiCo2-LDH.

[0107] Comparative Example 2

[0108] This comparative example provides a NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0109] Step 1, preparation of metal salt solution:

[0110] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0111] 2) 3.75 mmol of Ni(NO3)2·6H2O and 3.75 mmol of Co(NO3)2·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0112] Step 2, preparation of mixed solution:

[0113] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred. At the same time, the mixed system was ultrasonicated at an ultrasonic power of 700 W for 20 minutes to obtain a uniformly dispersed mixed solution.

[0114] Step 3, forming NiCo-LDH nanocatalyst by reflux reaction:

[0115] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a NiCo-LDH nanocatalyst.

[0116] That is, the difference between this comparative example and Example 1 is only that:

[0117] In this comparative example, no Ce salt is added, and the molar ratio of Ni salt to Co salt in this comparative example is 1:1, so the NiCo-LDH nanocatalyst obtained in the comparative example is marked as NiCo-LDH.

[0118] Comparative Example 3

[0119] This comparative example provides a NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0120] Step 1, preparation of metal salt solution:

[0121] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0122] 2) 5 mmol of Ni(NO3)2·6H2O and 2.5 mmol of Co(NO3)2·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0123] Step 2, preparation of mixed solution:

[0124] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred. At the same time, the mixed system was ultrasonicated at an ultrasonic power of 700 W for 20 minutes to obtain a uniformly dispersed mixed solution.

[0125] Step 3, forming NiCo-LDH nanocatalyst by reflux reaction:

[0126] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a NiCo-LDH nanocatalyst.

[0127] That is, the difference between this comparative example and Example 1 is only that:

[0128] In this comparative example, no Ce salt is added, and the molar ratio of Ni salt to Co salt in this comparative example is 2:1, so the NiCo-LDH nanocatalyst obtained in the comparative example is marked as Ni2Co-LDH.

[0129] Comparative Example 4

[0130] This comparative example provides a NiCo-LDH nanocatalyst, and its preparation method is as follows:

[0131] Step 1, preparation of metal salt solution:

[0132] 1) Mix 37.5 mL of ethylene glycol and 15 mL of deionized water to obtain a reaction solvent.

[0133] 2) 6.25 mmol of Ni(NO3)2·6H2O and 1.25 mmol of Co(NO3)2·6H2O were placed in the reaction solvent obtained above and mixed to obtain a metal salt solution.

[0134] Step 2, preparation of mixed solution:

[0135] 37.5 mmol of urea was added to the metal salt solution obtained above and stirred. At the same time, the mixed system was ultrasonicated at an ultrasonic power of 700 W for 20 minutes to obtain a uniformly dispersed mixed solution.

[0136] Step 3, forming NiCo-LDH nanocatalyst by reflux reaction:

[0137] The mixed solution was stirred and refluxed for 6 hours under an oil bath reaction condition of 90° C., and a solid component was obtained by centrifugation. The solid component was repeatedly washed by centrifugation with ethanol and deionized water until the pH of the supernatant in the centrifuge tube was 7, thereby obtaining a NiCo-LDH nanocatalyst.

[0138] That is, the difference between this comparative example and Example 1 is only that:

[0139] In this comparative example, no Ce salt is added, and the molar ratio of Ni salt to Co salt in this comparative example is 5:1, so the NiCo-LDH nanocatalyst obtained in the comparative example is marked as Ni5Co-LDH.

[0140] Experimental Section

[0141] (I) XRD test

[0142] The present invention uses Ce in Example 2 0.2 / NiCo-LDH, Ce of Example 4 0.4 / NiCo-LDH, Ce of Example 5 0.5 / NiCo-LDH and NiCo-LDH of Comparative Example 2 were taken as examples, and XRD tests were performed on them respectively, and the test results are as follows Figure 1 shown.

[0143] And by Figure 1 It can be seen that the Ce source appears in the form of CeO2, and the characteristic peak of LDH at 10° disappears with the increase of CeO2, proving that CeO2 destroys the layered structure of LDH.

[0144] (ii) TEM test

[0145] 1) Effect of different Ni / Co ratios on the morphology of prepared NiCo-based LDH nanocatalysts

[0146] The present invention characterizes and analyzes the morphology of NiCo2-LDH of Comparative Example 1, NiCo-LDH of Comparative Example 2, Ni2Co-LDH of Comparative Example 3 and Ni5Co-LDH of Comparative Example 4. The results show that compared with NiCo-LDH of Comparative Example 2, the layered plate crystallinity of the LDH lamellar structure of NiCo2-LDH of Comparative Example 1, Ni2Co-LDH of Comparative Example 3 and Ni5Co-LDH of Comparative Example 4 is poor. Therefore, when preparing NiCo-based LDH nanocatalyst by adjusting nickel salt and cobalt salt in an equimolar ratio, it is more conducive to improving the layered plate crystallinity of NiCo-based LDH nanocatalyst.

[0147] 2) Effect of Ce doping amount on the morphology of prepared NiCo-based LDH nanocatalysts

[0148] The present invention uses NiCo-LDH of Comparative Example 2 and Ce of Example 4. 0.4 / NiCo-LDH and Ce of Example 5 0.5 / NiCo-LDH was taken as an example, and TEM tests were carried out on them, and the test results were as follows Figure 2-Figure 4 shown.

[0149] Figure 2 This is the TEM image of NiCo-LDH of Comparative Example 2. It can be seen that when Ce is not doped, the generated LDH has a thinner layered structure and the lamellae are larger.

[0150] Figure 3 is Ce of Example 4 0.4 TEM image of / NiCo-LDH, compared with Figure 2 It can be seen that when the Ce doping amount is 0.4, the obtained LDH layer becomes thinner and the distribution of CeO2 on the layer is more uniform, indicating that after CeO2 is introduced into NiCo-LDH by the method of the present invention, CeO2 is uniformly doped in NiCo-LDH and the size of NiCo-LDH can be adjusted.

[0151] Figure 4 is Ce of Example 5 0.5 TEM image of / NiCo-LDH, compared with Figure 2 It can be seen that when the Ce doping amount is 0.5, the upper surface of the LDH layer obtained has a good crystal form, indicating that after introducing CeO2 into NiCo-LDH by the method of the present invention, the crystallinity of the NiCo-LDH layer can be adjusted.

[0152] (III) OER performance test

[0153] The OER performance test method adopted in the present invention is a three-electrode test: the counter electrode is a graphite rod, the reference electrode is a saturated calomel electrode, and the working electrode is glassy carbon coated with an active substance. The test is carried out under alkaline conditions, and the electrolyte solution is 1M KOH.

[0154] 1) Effect of different Ni / Co ratios on the OER performance of NiCo-based LDH nanocatalysts

[0155] The present invention tests and analyzes the OER performance of NiCo2-LDH of Comparative Example 1, NiCo-LDH of Comparative Example 2, Ni2Co-LDH of Comparative Example 3 and Ni5Co-LDH of Comparative Example 4. The results show that compared with NiCo2-LDH of Comparative Example 1, Ni2Co-LDH of Comparative Example 3 and Ni5Co-LDH of Comparative Example 4, NiCo-LDH of Comparative Example 2 shows the best OER performance, which indicates that when adjusting the nickel salt and the cobalt salt in an equimolar ratio to prepare the NiCo-based LDH nanocatalyst, it is more conducive to improving the OER performance of the NiCo-based LDH nanocatalyst.

[0156] 2) Effect of Ce doping amount on OER performance of NiCo-based LDH nanocatalysts

[0157] The present invention uses Ce in Example 2 0.2 / NiCo-LDH, Ce of Example 4 0.4 / NiCo-LDH, Ce of Example 5 0.5 / NiCo-LDH and NiCo-LDH of comparative example 2 were taken as examples, and their OER performance tests were carried out respectively, and the test results are as follows Figure 5 shown.

[0158] And by Figure 5 The test results show that compared with NiCo-LDH, Ce 0.2 / NiCo-LDH、Ce 0.4 / NiCo-LDH and Ce 0.5 / NiCo-LDH all have good OER performance.

[0159] It can also be seen that with the increase of Ce doping amount, the OER performance of the catalyst shows a trend of first increasing and then decreasing. 0.4 / NiCo-LDH catalyst showed the best OER performance at a current density of 100 mA cm -2When the overpotential of the catalyst is 345mV, it indicates that the Ce doping amount should not be too much or too little, and the molar ratio of nickel salt, cobalt salt and cerium salt should be 1:1:0.1-0.5, so that the electrocatalytic performance of LDH can be improved by the appropriate amount of CeO2 doped. The molar ratio of nickel salt, cobalt salt and cerium salt is more preferably 1:1:0.4.

[0160] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a CeO2-loaded NiCo-LDH nanocatalyst, characterized in that: The following steps are involved: Using cerium salt as a doping source, uniformly dispersing it, nickel salt and cobalt salt in a reaction solvent to obtain a metal salt solution; Using urea as a precipitant, uniformly dispersing it in the metal salt solution to obtain a mixed solution; Under stirring conditions, the mixed solution is subjected to a reflux reaction at 85° C. to 95° C., so that the nickel ions and cobalt ions provided by the nickel salt and the cobalt salt react with the urea to precipitate to form NiCo-LDH, and at the same time, the cerium salt is converted into CeO2 in the form of nanoparticles on the surface of NiCo-LDH, thereby obtaining the CeO2-loaded NiCo-LDH nanocatalyst.

2. The preparation method according to claim 1, characterized in that The cerium salt is one or more of cerium chloride, cerium nitrate and cerium sulfate.

3. The preparation method according to claim 1, characterized in that: The nickel salt is one or more of nickel nitrate, nickel sulfate and nickel chloride.

4. The preparation method according to claim 1, characterized in that: The cobalt salt is one or more of cobalt nitrate, cobalt sulfate and cobalt chloride.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the nickel salt, the cobalt salt and the cerium salt is 1:1:0.1-0.

5.

6. The preparation method according to claim 1, characterized in that: The reaction solvent is a mixed solvent of ethylene glycol and water in a volume ratio of 2 to 3:

1.

7. The preparation method according to claim 1, characterized in that: The molar ratio of the urea to the cobalt salt is 0.037-0.038:

1.

8. The preparation method according to claim 1, characterized in that: The dispersion is carried out by ultrasonic coordinated stirring, and the ultrasonic power is 600W to 800W, and the ultrasonic time is 10min to 30min.

9. The preparation method according to claim 1, characterized in that: The reflux reaction time is 4h to 8h.

10. A CeO2-supported NiCo-LDH nanocatalyst prepared by the preparation method according to any one of claims 1 to 9.